Evaluation of physicians' skills in breaking bad news to cancer patients - Zahra Mostafavian (Journal of Family Medicine and Primary Care, 2018)
Background: Delivering bad news to patients is one of the most difficult tasks of physicians that play a big role in the process of treatment and cooperation of patients. The objective of this study is to evaluate the ability and skills of physicians in delivery bad news to cancer patients. Methods: This study is a cross-sectional study performed on 70 specialist physicians in two hospitals of Mashhad in 2016. Data were collected by Persian questionnaire of SPIKES included 16 questions and were analyzed by SPSS software. Results: In this study, among the questionnaire items, the most prevalent item was not giving the bad news by phone (100%) and the least prevalent item was putting the hand on the shoulder (24.3%). This study showed that 81.4% of doctors agreed on giving the bad news in private, 72.9% agreed on giving relative hope to patients and 67.1% agreed on evaluating patients knowledge of his/her disease when giving bad news. Conclusion: The results of this study show that the ability of physicians in giving bad news is not enough in some aspects. Therefore, holding educational courses during physicians' education and after graduation are recommended to increase patients' trust and decreasing worries and inconvenience of physicians in difficult situations of delivering bad news.